THE EFFECT OF COMPETENCY, WORK DISCIPLINE AND COMPENSATION ON EMPLOYEE PERFORMANCE OF PT. KILAT UTAMA INDONESIA - Musa, Chalid Imran (Nusantara Economics and Entrepreneurships Journals, 2025)
This study aims to 1) determine the Influence of Competence, Work Discipline and Compensation on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch. 2) to determine the Influence of Competence on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch. 3) to determine the Influence of Work Discipline on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch. 4) to determine the Influence of Compensation on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch. This type of research is Associative research. The variables used in this study are competence, work discipline and compensation as independent variables and employee performance as dependent variables. The population of the study was 70 employees with a sample of 60 respondents. The data used is Primary data with data collection techniques in the study by distributing questionnaires. Data analysis used in this study is multiple linear regression analysis. The results of the study indicate that 1) There is a positive and significant influence of Competence, Work Discipline and Compensation on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch, 2) There is a positive and significant influence of Competence on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch, 3) There is a positive and significant influence of the Influence of Work Discipline on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch, 4) There is a positive and significant influence of Compensation on Employee Performance of PT. Kilat Utama Indonesia Palembang Branch.